Efecto de las distancias de siembra en la Ipecacuana o Raicilla (Cephaelis ipecacuanha Rich.) (ING) - Rodríguez N., Hernán (1990)
An experiment was performed to determine the appropriate planting distances of Ipecac plants (Cephaelis ipecacuanha Rich) grown under a tropical rain forest canopy. Plant survival at the uprooting age (2 ½ years) and dry root weight was found to be influenced by planting distances. The percentage of surviving plants increased linearly (P< 0.01) as distance between rows or between plants within a row increased. Three criteria useful to choose planting distances of Ipecac are discussed: 1)age and size of the plants at the uprooting time; 2)spread of structures of fungi known to infect this crop in Costa Rica as a consequence of heavy rain drops striking infected soil or plant tissue; 3)the benefit/cost ratio. Planting distances of 20.0 cm between rows and 7.5 cm between plants yielded the highest dry root weight and thus are recommended, but longer distances between rows should be tested.